Do different types of FDI strategies spur productivity and innovation capability growth? Evidence from Taiwanese manufacturing firms - Lin, Hui-Lin; Hsiao, Yi-Chi; Lin, Eric S. (Journal of Business Economics and Management, 2014)
Based on different motivations for engaging in outward FDI, this study divides firms' outward FDI into five types: non-FDI, FDI, defensive only outward FDI, expansive only outward FDI, and both defensive & expansive outward FDI simultaneously, and proposes four hypotheses to evaluate their relative strength in terms of firm productivity and innovation capability. The propensity score matching estimator based on a uniquely compiled Taiwanese manufacturing data set shows that, as firms engage in outward FDI, they have higher productivity growth rates compared to non-FDI firms. As for the further disengagement of the impacts of outward FDI, our empirical results indicate that expansive outward FDI tends to strengthen firms' productivity growth, while such a growth-boosting effect is not statistically significant for defensive outward FDI. Moreover, as far as firms undertaking defensive & expansive outward FDI simultaneously are concerned, we also find a positive and significant impact of outward FDI on productivity growth, but the effect is not as large as that for firms engaging solely in expansive outward FDI. This may imply that defensive outward FDI has some adverse effects on firms' productivity growth. As firm performance is measured by innovation growth, the average treatment effects are all significantly positive regardless of the type of outward FDI strategies. Nevertheless, engaging in defensive outward FDI is less advantageous to innovation growth than the expansionary outward FDI, as well as to defensive & expansive outward FDI simultaneously.